Differential Effects of Platelets Selectively Activated by Protease-Activated Receptors on Meniscal Cells. Issue 1 (January 2020) - Xu, Hongyao; Zou, Xiangjie; Xia, Pengcheng; Aboudi, Mohammad Ahmad Kamal; Chen, Ran; Huang, He
Background: Meniscal injury is very common, and injured meniscal tissue has a limited healing ability because of poor vascularity. Platelets contain both pro- and anti-angiogenic factors, which can be released by platelet selective activation. Hypothesis: Platelets release a high level of vascular endothelial growth factor (VEGF) when they are activated by protease-activated receptor 1 (PAR1), whereas the platelets release endostatin when they are activated by protease-activated receptor 4 (PAR4). The PAR1-treated platelets enhance the proliferation of meniscal cells in vitro and promote in vivo healing of wounded meniscal tissue. Study Design: Controlled laboratory study. Method: Platelets were isolated from human blood and activated with different reagents. The released growth factors from the activated platelets were determined by immunostaining and enzyme-linked immunosorbent assay. The effects of the platelets with different treatments on meniscal cells were tested by an in vitro model of cell culture and an in vivo model of wounded meniscal healing. Results: The results indicated that platelets contained both pro- and antiangiogenic factors including VEGF and endostatin. In unactivated platelets, VEGF and endostatin were contained inside of the platelets. Both VEGF and endostatin were released from the platelets when they were activated by thrombin. However, only VEGF was released from the platelets when they were activated by PAR1, and only endostatin was released from the platelets when they were activated by PAR4. The rat meniscal cells grew much faster in the medium that contained PAR1-activated platelets than in the medium that contained either PAR4-activated platelets or unactivated platelets. The wounds treated with PAR1-activated platelets healed faster than those treated with either PAR4-activated platelets or unactivated platelets. Many blood vessel–like structures were found in the wounded menisci treated with PAR1-activated platelets. Conclusion: The PAR1-activated platelets released high levels of VEGF, which increased the proliferation of rat meniscal cells in vitro, enhanced the vascularization of menisci in vivo, and promoted healing of wounded menisci. Clinical Relevance: Our results suggested that selective activated platelets can be used clinically to enhance healing of wounded meniscal tissue.